Wear and corrosion properties of pure aluminum reinforced with (B4C + Spent Catalyst) composite. (2022) - Pragathi, P.; Elansezhian, R.
Abstract: In a recent study, the spent catalyst from an oil refinery is used for reinforcing the aluminum matrix. The corrosion and wear behavior of the aluminum reinforced with (B4 C + spent catalyst) was investigated in the present research. The stir casting process is used to prepare the reinforcing of various weight percentages of boron carbide (2.5, 5, 7.5, and 10) and spent catalyst. The sliding wear test was carried out for 10 min in a pin-on-disk setup with a uniform load of 10 N and a steady sliding velocity of 5 m/s. Corrosion tests were performed in a salt-spray bath for 300 h. By using the weight loss procedure, wear and corrosion rate have been calculated. SEM image is used to study composite morphology characterization. It was also shown to reduce the wear and corrosion rate for fabricated composites compared to the base metal at 10 wt% (B4 C + spent catalyst), excellent wear and corrosion behaviour are achieved..